Depicting time: Visualizing the duration of existence and facts in past, present and future - Zantides, Evripides; Papadima, Aspasia (My University, 2013)
Time as duration, as a unit of measurement of duration, as a natural unit to express the depiction of individual moments, phenomena and events, has constituted a philosophical and scientific challenge to humanity. The conversion and organization of the notion of time into a visual form is a continuous experimental process. This study presents a theoretical and historical overview of the depiction of time, and addresses the visualization of duration from analog to digital form, and the everyday, commercial and conjectural mapping of time by analyzing specific audiovisual examples from a theoretical and visual-arts historic perspective. Through philosophy, religion, fine and applied arts, as well as modern audiovisual communication, various ways of signaling time are selectively presented and discussed.
Keywords: Time; Visualization; Depiction; Visual arts history